Awareness of waqf among students: The case of Universiti Malaysia Kelantan - Azlin Nadiah Omar; Farah Anisah Abdul Aziz; Nur Intan Baiduri Mohd Zam (2022)
Waqf provides significant benefits not just to the endower but also to society as a whole. In Islam, the term waqf refers to the ownership of property and its preservation for the limited benefit of charity, as well as the prohibition of its use or disposition for any other purpose. The main purpose of the study is to examine whether or not factor of awareness predict awareness of waqf among Universiti Malaysia Kelantan students. Besides, the purpose of the study also to identify there is a relationship between awareness of waqf among Universiti Malaysia Kelantan students and informative influence, convenience and attitude. The study uses four Statistical Package for the Social Sciences (SPSS) to analyze the data including descriptive analysis, cross tabulation, reliability analysis, correlation analysis, and multiple linear regression analysis. The data was gathered by distributing online questionnaire to 346 students of Faculty Entrepreneurship and Business, Universiti Malaysia Kelantan. The results of the study indicate that students have good understanding and awareness of waqf. In addition, the results show that overall, there is positive and significant relationship between awareness of waqf and informative influence, convenience and attitude. Based on the analysis of data and information presented by the participating students, the various proposals for improvements were proposed. However future study should be conducted around outside of Universiti Malaysia Kelantan. Second, there are only three factors of awareness in this study and all three are significant. So, further studies are needed to look into additional factors that might explain the variance in waqf awareness such religiousness, intention and knowledge. Third, future study should look at what motivates people to give and contribution of money continuously, since different forms of waqf and why people choose to endow waqf from the viewpoint of the endower and also the waqf institutes.